Case report: Durable response from tegafur/gimeracil/oteracil (S-1) combined with fruquintinib and sintilimab as a third-line treatment for MSS metastatic colorectal cancer with a BRAF V600E mutation - He, Chunxia; Chi, Jiaxin; Du, Zhihua; Zhuang, Zhenjie; Li, Liuning (Frontiers in Oncology, 2024)
Patients with microsatellite stable (MSS) metastatic colorectal cancer (mCRC) who fail first- and second-line treatments face significant challenges in third-line therapy, where monotherapies often yield poor outcomes and limited survival benefits. The prognosis is particularly poor for mCRC with the unique molecular subtype of BRAF V600E mutation. This report describes sustained benefits from a third-line treatment regimen (SFS) combining tegafur/gimeracil/oteracil (S-1), fruquintinib, and sintilimab in a patient with BRAF V600E-mutated MSS mCRC. A 23-year-old woman was admitted with dizziness, and enhanced computed tomography (CT) and colonoscopy revealed colon cancer. Based on pathological and genetic testing, the final diagnosis was colon adenocarcinoma with lymph node and liver metastases (cT3N1M1, stage IVc, BRAF-V600E(+), MSS type). Following progressive disease (PD) after FOLFOX chemotherapy and surgery, the patient received 40 cycles of the SFS regimen (S-1 60 mg bid po d1–14 + fruquintinib 3 mg qd d1–21 + sintilimab 200 mg ivd q3w), achieving stable disease (SD). At the most recent follow-up, the patient has remained in sustained remission for over 3 years. The SFS regimen may be an attractive therapeutic strategy for patients with BRAF V600E-mutated MSS mCRC, warranting further evaluation in a larger patient cohort. We have registered a related clinical study (registration number: ChiCTR2300079188) and hope that the results will bring new hope for patients with MSS mCRC.